Woodland craft - Law, Ben. (Lewes, East Sussex, UK : Guild of Master Craftsman Publications, 2015)
Accompany woodsman Ben Law as he celebrates the amazing diversity of craft products made from materials sourced directly from the woods. Including brooms, rakes, pegs, spoons, chairs, baskets, fencing, yurts and even a caravan, the items are hewn from freshly cut green wood, shaped by hand and infused with a simple, rustic beauty. Detailed instructions and advice are given for each craft, along with essential knowledge about tools and devices. Accompany woodsman Ben Law as he celebrates the amazing diversity of craft products made from materials sourced directly from the woods. With fascinating information on the history, language and traditions of the crafts, coppice management and tree species, this book teaches about all aspects of the low-impact woodland way of life.
The woodland resource -- Directory of tree species -- Crafts for farm and garden -- Wood fuel -- Crafts for building -- Domestic crafts -- Tools and devices for woodland crafts.
JHS
Text in English
Keywords: Woodwork; Woodworking tools; Handicraft; Forest management; Forest conservation